Pengolahan Limbah Pisang Berbasis Zero Waste pada Kelompok Tani Pao Kalikie - Andi Muhammad Irfan Taufan Asfar; Romi Adiansyah; Ahmad Zailan; Andi Muhamad Iqbal Akbar Asfar; Andi Nurannisa (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The potential of Maggenrang Village, Kahu Sub-district, Bone Regency as a center for plantation commodities is quite large, especially fruit plantations in the form of bananas. However, banana processing often leaves waste that is not properly processed. Therefore, the implementation of this Community Partnership Program (PKM) activity aims to empower the Pao Kalikie Farmer Group through diversification of processed bananas with a zero waste approach. The activity implementation method consists of three stages, namely counseling, training, and mentoring. The form of activity evaluation can be seen from the results of partner preferences using questionnaires and descriptive analysis. The results of the service showed an increase in partner knowledge and skills in processing bananas into high-value products, namely banana stems and fruits into chips, and the remaining stems and fronds into ecoenzyme. Partner knowledge after the implementation of the activity increased by 92%, and partner skills increased by 90%. This PKM has a positive impact in building the entrepreneurial spirit of partners.